VALIDAÇÃO DE PLANO TERAPÊUTICO DE CUIDADO PARA GESTANTES DE ALTO RISCO - Flain, Viviane Queiroz (2019)
Introduction: The performance of the nurse in high-risk antenatal care is a concern with the mother and child health care. The nursing care through the nursing process is a tool of care for the care, aiming at the realization of a therapy of care and pregnancy. In this context, includes the therapeutic plan of care that enables the strengthening the network of care, making the reality and the reference between the services involved, as well as foster care. In this case, the question: is the Therapeutic Care Plan for people at high-risk physiotherapeutic? This study is justified due to the gap found in the process of pervasive prenatal high risk, as well as latent work in Networks of Care. General objective: To validate a therapeutic plan of care for high-risk pregnant women, contemplating the stages of the nursing process. Specific Objectives: the therapeutic plan of care validated for the health professionals of the Maternal Child Care Line (MCCL); Apply the therapeutic plan of care with the users of the High Risk Pregnancy Clinic (HRPC); To evaluate the effectiveness of the therapeutic plan of care as work tool in net, through the data filled out by the professionals in the way of the net of attention through where the patient. Method: Methodological researches, accomplished from October 2018 to January of 2019, in two different moments: the first refers the validation of the Therapeutic Plan of Care, through the methodological research and the second, characterized by the implementation and evaluation of the same, through the Assistance Convergent Research (ACR). It was used a Delphi technique for content validation with the participation of seven health experts. We evaluated the items for the validation of the instrument, using a Likert scale and the Validity Index of Contents equal to 1.0, already in the first round. Results: the article 01, includes an integrative literature review, which aimed to know what is in the Brazilian scientific literature about systematization of nursing assistance. The article 02, referring to the research product, which aimed to review, validate and evaluate a therapeutic plan of care for pregnant women at high risk. Final considerations: The therapeutic care plan is an important tool for networking and health care, very used to strengthen the link between health professionals through whom a pregnant woman circulates. What hinders its use appropriately are the gaps in services, such as a lack of professionals, excessive work load, difficulty in keeping the pregnant women at high risk linked to the basic health unit. Product generated: therapeutic plan of care for pregnant women at high risk reviewed, validated as to content and appearance. Product Applicability: The instrument was implemented in prenatal care by the multiprofessional team, with high-risk pregnant women assisted at the High Risk Prenatal Outpatient Clinic (AGAR) of a reference university hospital for the municipalities of the 4th Regional Health Coordination in Rio Grande do Sul State, constituting a communication link with Primary Care. In addition, it favors the instrumentation of pregnant women for self-care, through guidance and referrals to specialized services.